Can desert phreatophytic trees enhance recharge through sediment-clogged reservoirs of recharge dams in Arabia? - N. Al-Kharousi; A.R. Kacimov; A. Al-Maktoumi; S.S. Al-Ismaily (International Journal of Sediment Research)
Sidr (Christ-thorn) phreatopytic-xerophitic wild trees growing in the reservoir area of the Al-Khoud groundwater recharge/flood protection dam in Muscat (Oman) were surveyed. Trees’ loci, heights and stem diameters were measured. Soil profiles were described in two pedons (trenches) excavated near two pilot trees. A remarkable increase in infiltration rate was observed when double-ring infiltrometers were placed near the tree stems and at the bottom of the trenches. Sap flow metering conducted on one tree over a period of 9 months resulted an average rate of 12.5 L/d. This value was used to evaluate the reservoir water balance, considering it as the difference between infiltration of ponded post-flash-flood water and transpiration. Sidr trees are recommended as excellent eco-engineers, that can alleviate the negative impact of reservoir bed siltation by enhancing the infiltration-recharge of the underlying aquifer.